2013
DOI: 10.1089/lap.2012.0310
|View full text |Cite
|
Sign up to set email alerts
|

Totally Laparoscopic Versus Open Gastrectomy for Gastric Cancer: A Matched Cohort Study

Abstract: Background: The role of laparoscopic surgery for the treatment of gastric cancer is still controversial, particularly in terms of oncologic efficacy. The aim of this study was to compare short-term outcomes of laparoscopic and open resection for gastric cancer at a single Western institution. Subjects and Methods: This study was designed as a matched cohort study from a prospective gastric cancer database. Forty-one patients undergoing laparoscopic gastrectomy for gastric cancer between June 2008 and January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 38 publications
1
69
0
2
Order By: Relevance
“…Additionally, lymph node dissection did not differ between the minimally invasive and open group. This is in accordance with several Western studies . However, minimally invasive gastrectomy was mostly performed on patients with stage IB cancer, making it susceptible for bias.…”
supporting
confidence: 90%
“…Additionally, lymph node dissection did not differ between the minimally invasive and open group. This is in accordance with several Western studies . However, minimally invasive gastrectomy was mostly performed on patients with stage IB cancer, making it susceptible for bias.…”
supporting
confidence: 90%
“…Kim et al. (2013) compared 139 totally laparoscopic total gastrectomy operations with 207 patients undergoing laparotomy, noting that the return of oral diet was significantly faster in laparoscopic surgery (p=0.018) 13 , corroborating the data from many studies in the literature 6 , 20 , 26 . On the other hand, Jeong et al (2013) in their series found no significant difference with regard to the time of return to oral diet 12 .…”
Section: Discussionmentioning
confidence: 74%
“…Series of published reports have addressed the estimated blood loss during the operation. In general, the blood loss during the laparoscopic procedure was significantly lower than during the open procedures 5 , 6 , 9 , 21 , 26 , 27 , 29 . In this study there was no significant difference as to the average of blood units received in both groups (p=0.127).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…An important previous finding is that laparoscopic gastrectomy showed similar results to open gastrectomy with regard to quality of oncological resection, as measured by the number of retrieved lymph nodes and 5-year survival, 7 whereas patient recovery was faster and admission duration shorter. 8,9 However, these studies were underpowered and do not take into account neoadjuvant therapy and long-term follow-up.…”
mentioning
confidence: 99%